2007
DOI: 10.1021/ja070032n
|View full text |Cite
|
Sign up to set email alerts
|

Growth Dynamics of CdTe Nanoparticles in Liquid and Crystalline Phases

Abstract: Normally the size dependence of the chemical potential is used to explain the growth dynamics of semiconductor nanoparticles. Instead we show that very small CdTe nanoparticles continue to grow at high dilution, the growth rate is virtually independent of monomer concentration, nucleation continues after the growth of larger particles has saturated, and the growth rate has a much greater nonlinear dependence on particle size than predicted by theory. We suggest that nanoparticle growth is fast in the liquid ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 33 publications
4
49
1
1
Order By: Relevance
“…The transition radius changed with temperature. The growth dynamics could not be explained by the depletion of monomers during growth, or by the size dependence of the chemical potential, or by Ostwald ripening, because very small particles continued to grow at high dilution, the growth rate was virtually independent of monomer concentration, nucleation continued after the growth of larger particles has saturated and the growth rate had a much greater nonlinear dependence on particle size than predicted by theory 11. Instead, we suggested that particle growth is influenced by a phase transition of the particles from a liquid to a crystalline state.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The transition radius changed with temperature. The growth dynamics could not be explained by the depletion of monomers during growth, or by the size dependence of the chemical potential, or by Ostwald ripening, because very small particles continued to grow at high dilution, the growth rate was virtually independent of monomer concentration, nucleation continued after the growth of larger particles has saturated and the growth rate had a much greater nonlinear dependence on particle size than predicted by theory 11. Instead, we suggested that particle growth is influenced by a phase transition of the particles from a liquid to a crystalline state.…”
Section: Introductionmentioning
confidence: 81%
“…10 The critical radius changes during growth as the monomer concentration is depleted. However, we pointed out recently that, for the preparation of CdTe NCs using the colloidal technique, the size dependence of the chemical potential with or without Ostwald ripening does not satisfactorily describe the growth kinetics 11. We investigated the preparation of several batches of CdTe nanoparticles grown at 140 °C where [Te] was varied over a wide range (×27), whilst other growth parameters remained the same.…”
Section: Introductionmentioning
confidence: 99%
“…24 With further prolonging the reaction time, smaller particles started to dissolve thus releasing monomers that were then used up by the larger particles, leading to broadening the size distribution and increasing the number of surface defects. Therefore the PL intensity was low in this stage and it would gradually increase with the QDs growth.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Based on studies, temperature is a critical factor and has significant effect on the crystal growth, structure and optical properties of the QDs. It could be said that the growth of nanoparticle with perfect surface structure would be possible by increasing the synthesizing temperature resulting better photoluminescence properties get better [5]. It is considerable that the quantum yield (QY) and life time of QDs do not increase continuously with elevating the growth temperature.…”
Section: Introductionmentioning
confidence: 99%